Scrap reduction study for automotive stamping - Mohd Hilman, Sobhi (2008)
This thesis investigate and analysis the reduction of scrap in automotive manufacturing parts. In this project it concern about the car door production and process. There are two types processes in making car door, first is stamp door which using the stamping process as a main process and second is sash door which using roll forming and stamping process in operating. In order to obtain the data and information about both process the experiment have been done and analyze the data. The data including time assembly, quantity part, die and scrap produced .Beside that both processes have been analyzed from manufacturing aspect including material cost, material and machine. This result presenting in SWOT analysis and QCD analysis to make comparison and choosing the best process .After the analysis, stamp door process is prefer based on faster in assembly and die quantity compare to sash door which more quantity dies needed and slow in assembly process. Otherwise, sash door have advantage in reducing scrap and small quantity in parts needed. For overall it can be conclude that stamp door is the best process for giving maximizes profit to the company by reducing the cost and achieve the objective of this project.